Immune to happiness – inflammatory process indicators and depressive personality traits - Talarowska, Monika E. (Arch Med Sci, 2019)
INTRODUCTION: Nowadays, depression is conceptualized as an immune-inflammatory and oxidative stress disorder associated with neuroprogressive changes as a consequence of peripherally activated immune-inflammatory pathways, including peripheral cytokines and immune cells which penetrate into the brain via the blood barrier, as well as nitro-oxidative stress and antioxidant imbalances. The aim of this study was to investigate whether personality traits predisposing to a depressive episode (hypochondria, dysthymic, hysteria) are associated with changes in peripheral gene expression for selected indicators of inflammation and oxidative balance. MATERIAL AND METHODS: One hundred four people meeting the diagnostic criteria specified for a depressive episode took part in the study. Selected scales of the Minnesota Multiphasic Personality Inventory (MMPI-2) were used to measure personality traits. Expression at the mRNA and protein level for manganese superoxide dismutase (MnSOD), myeloperoxidase (MPO), cyclooxygenase 2 (COX-2), inducible nitric oxide synthase (iNOS), and metalloproteinases 2 and 9 (MMP-2, MMP-9) was examined. RESULTS: Scales for the neurotic triad of the MMPI-2 test correlated significantly with the expression at the level of mRNA and protein for MnSOD, MPO and metalloproteinases 2 and 9. CONCLUSIONS: The scales specified for the neurotic triad of the MMPI-2 test correspond substantially with the expression of MnSOD, MPO and metalloproteinases 2 and 9 at the mRNA and protein levels in the group of patients suffering from depression.